(untitled) (Minerva, 2019)
Review: József Herman, Linguistic Studies on Latin: selected papers from the 6th International Colloquium on Latin Linguistics, Budapest, 23-27 March 1991, Amsterdam-Philadelphia, 1994, 421 pp.